PERTANGGUNGJAWABAN PIDANA PELAKU MALAPRAKTIK KECANTIKAN YANG MENYEBABKAN KERUGIAN PADA PASIEN - Virshel Enggyari Atsila (2023)
Malpractice is a fault in professional standards that causes someone to suffer harm. One of the most common types of malpractice is medical malpractice. A medical practice that is commonly performed today is about beauty needs that are attempted by treatments. The medical demand is not balanced with the professionalism of doctors and health workers in taking treatment so that malpractice occurs which causes harm to patients. This is reinforced by the existence of several cases of beauty malpractice where the victim suffers harm in the form of injury or death. Therefore, researcher is interested in researching two problems. The first is, What are the factors that cause beauty medical malpractice and second, What is the criminal responsibility of beauty medical malpractice that causes harm to patients. Researcher use the normative juridical research method with a statute approach and data collection through library research from primary, secondary and tertiary legal materials. The results of this paper are many factors that can caused by beauty medical malpractice because these factors not only came from the perpetrator but also came from the victim. These factors include economic, social, legal, and individual factors. The responsibility for beauty malpractice can be classified into three (3) forms, namely due to intent, negligence and recklessness, all of that must be proven. To hold the perpetrator responsible, beauty malpractice must cause direct harm from the treatment. This treatment must result in severe injury or death of the patient. The punishment for the perpetrator is sourced from the Indonesian Criminal Code and specific laws (lex Specialis) depending on the actions taken. Keywords: Criminal Responsibility, Beauty Malpractice